Critique of Digital Historical Sources on TikTok: A Case Study of Verifying Prince Diponegoro’s Narrative on the @aslimojokertocom Account - Haikal, Ahmad Hasanain; Zuhdi, Ahmad (Proceedings of International Conference on Islamic Civilization and Humanities, 2026)
The development of social media platforms, especially TikTok, has opened new spaces for the massive dissemination of historical content to the public. However, such content does not always meet adequate standards of historical accuracy. This study aims to analyze and evaluate the historical narrative about Prince Diponegoro disseminated through the TikTok account @aslimojokertocom using historical source criticism, including external criticism (authenticity) and internal criticism (content credibility). The method used is the historical method with a netnographic approach and content analysis. The analysis found a fatal chronological error: the content claims that Prince Diponegoro visited a location in 1865, whereas historically, he had already passed away on January 8, 1855, in Makassar, as a prisoner of the Dutch Colonial Government. This error reflects the complete absence of source verification in content production and has the potential to create deeply misleading understandings of Nusantara Islamic history among millions of social media users. This study recommends the importance of applying historical source criticism when consuming digital historical content and the necessity of historical literacy education for social media users.